Devices and methods for direct visual detection and readout of single nucleic acid molecules - Ismagilov,RF; Rodriguez,Manzano J; Karymov,M; Selck,DA; Begolo,S; Jue,EB; Zhukov,DV (2018)
The present invention relates to methods, computer readable medium and systems for detecting and counting single nucleic acid molecules confined in nanoliter volumes using an unmodified camera, such as a cell phone camera. In particular, it identifies colorimetric amplification-indicator dyes that are compatible with the spectral sensitivity of standard mobile phones. The invention further provides an optimal ratiometric image-process for a selected dye to achieve a readout that is robust to lighting conditions and camera hardware and provides unambiguous quantitative results, even for colorblind users.